2012
DOI: 10.1016/j.sste.2012.02.002
|View full text |Cite
|
Sign up to set email alerts
|

A research agenda: Does geocoding positional error matter in health GIS studies?

Abstract: Until recently, little attention has been paid to geocoding positional accuracy and its impacts on accessibility measures; estimates of disease rates; findings of disease clustering; spatial prediction and modeling of health outcomes; and estimates of individual exposures based on geographic proximity to pollutant and pathogen sources. It is now clear that positional errors can result in flawed findings and poor public health decisions. Yet the current state-of-practice is to ignore geocoding positional uncert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 54 publications
(74 reference statements)
0
83
0
2
Order By: Relevance
“…The incompleteness of temporally or spatially sampled location data is also a considerable factor leading to uncertainty issues in GIScience [53,54], raising concerns regarding how uncertainties could affect the findings [55,56]. Some researchers think that long periods of time help increase sample size; Jacobs [57] notes that these data are large numbers of repeated observations over time and/or space and may not get rid of the sparse issue.…”
Section: Representative Issues Of Big Datamentioning
confidence: 99%
“…The incompleteness of temporally or spatially sampled location data is also a considerable factor leading to uncertainty issues in GIScience [53,54], raising concerns regarding how uncertainties could affect the findings [55,56]. Some researchers think that long periods of time help increase sample size; Jacobs [57] notes that these data are large numbers of repeated observations over time and/or space and may not get rid of the sparse issue.…”
Section: Representative Issues Of Big Datamentioning
confidence: 99%
“…Here we focus on the positional error, as it is one of the most prominent types of errors in many context and application (Ariza-LĂłpez & RodrĂ­guez-Avi, 2015b;Drummond, 1995) and subject to intensive research (e.g. Biljecki, Heuvelink, Ledoux, & Stoter, 2015;Cheung & Shi, 2004;Chow, Dede-Bamfo, & Dahal, 2016;Jacquez, 2012;McKenzie, Hegarty, Barrett, & Goodchild, 2016;RuizLendĂ­nez, Ariza-LĂłpez, & Ureña-CĂĄmara, 2016). We term the combination of the acquisitioninduced and positional errors as combined error, and describe them in further detail in the next subsections.…”
Section: Decoupling Errorsmentioning
confidence: 99%
“…Quality aspects are vital for geocoding and can be described by the completeness (the share of the records that are geocoded), the concordance to the geographic unit (the share of geocoded records that are linked to an incorrect geographic unit), and the positional accuracy of the reference data. Although several studies have been reported on this issue in modern demography and epidemiology (e.g., Zandbergen 2007Zandbergen , 2009Griffith et al 2007;Mazumdar et al 2008;Vieira et al 2010), this issue is a rather neglected topic that requires additional attention (Jacquez 2012). In addition, with a few exceptions (e.g., Delmelle et al 2014) little attention has been focused on the temporal quality of the geocoding of longitudinal data.…”
Section: Geocoding Of Demographic Databasesmentioning
confidence: 99%